MICROBIAL COUNT ASSESSMENT OF SOME COMMERCIAL YOGHURTS SOLD IN SAMARU, ZARIA METROPOLIS, KADUNA STATE - Girigisu, M.; Sani, R.T.; Zahradeen, D.; Ibrahim, U. M.; Achi, N.P.; Rekwot, G.Z.; Idowu, W.; Ishiaku, Y. M.; Ahmed S. A.; Idris, I.D. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
In view of the importance attached to microbiological safety and identification of contamination associated with yoghurt production and distributions, this study titled "microbial counts assessment of commercial yoghurts sold in Samaru, Zaria metropolis, Kaduna state was conducted. Seven different brands of NAFDAC certified yoghurts from different retailers were purchased in Samaru of Sabon Gari Local Government Area of Zaria, Kaduna State. They were labelled and conveyed to the Department of Microbiology at Ahmadu Bello University, Zaria, in ice packs for microbiological analysis. Morphological Characterization and Microscopic Observation of the Bacteria, which consist of Gram Staining and Biochemical Characterization where carried out. The result revealed that, bacterial counts in the seven sampled brands of yogurts ranges from 1.20E+06(SB) to 3.70E+06 (SC), E. coli counts ranged from 1.00E+04 (SG) - 6.00E+04(SD), Fungal counts fall to a range of 1.00E+04 (SE) - 8.00E+04 (SB), Staphylococcal ranged between 6.00E+04 (SB) - 1.10E+05 (SA and SG) while Coliform viable count was recorded only in sample SB with value of 1.00E+04. Of all obtainable outcomes, only total bacterial count falls within regulatory limits specified by International Organization for Standardization, ISO, 2017 and 2018. E-Coli, Fungal, Staphylococcal and Coliform counts all yield outputs at many folds above their respective ISO regulatory limits. These findings suggest that, despite bearing NAFDAC label by each of these products, the yogurt being sold in Samaru cannot be said to be hygienically suitable for consumption and thus may pose risk to human health. Further studies of microbial counts of certified yogurts sold in Samaru is recommended to be able to verify observations made in this study.